Colorectal Cancer From Pathogenesis to Treatment - Rodrigo, Luis (IntechOpen, 2016)
Colorectal cancer (CRC) is a major health problem because it represents around 10% of all cancers and achieves a worldwide estimate of 1.4 million newly diagnosed cases annually, resulting in approximately 700,000 deaths. Approximately 19-31% of patients present liver metastases. At diagnosis, a further 23-38% will develop extra-hepatic disease. Over the past decade, the widespread use of modern chemotherapeutic and biological agents, combined with laparoscopic surgical techniques, has improved the prognosis of metastatic CRC. A better understanding of the biology of the tumor, along with high efficiency of diagnostic and therapeutic methods, as well as the spread of screening programs, will improve the survival of the CRC patients in the near future.